Dispersion and gelation behavior of alumina suspensions with Isobam. Issue 10 (July 2018) - Lu, Yuju; Gan, Ke; Huo, Wenlong; Lv, Lin; Liu, Jingjing; Zhang, Xiaoyan; Yan, Shu; Yang, JinLong
Abstract: As a copolymer of isobutylene and maleic anhydride, Isobam, a newly-developed gelling agent, plays a significant role in ceramic forming process. However, dispersion and gelation behavior of Isobam has not been discussed in detail yet. To investigate the influence of other dispersants, pH and electrolytes on dispersion and gelation behavior of Isobam, zeta potential, viscosity and modulus curves during gelation were measured from 50 vol% alumina suspensions with 0.1–0.7 wt% Isobam. A two-step bridging mechanism is proposed to explain the gelation behavior of Isobam, providing guidance on usage of Isobam in combination of other additives to achieve suspensions with high solids loading and adjustable gelation characteristic.